Corporate Governance for Crooks? The Case for Corporate Virtue - Margit Osterloh; Bruno S. Frey (Center for Research in Economics, Management and the Arts (CREMA), 2005)
Corporate scandals are reflected in excessive top management compensation and fraudulent accounts. These scandals cause an enormous amount of damage, not only to the companies affected, but also to the market economy as a whole. As a solution, conventional wisdom suggests more monitoring and sanctioning of management. We argue that these efforts will create a governance structure for crooks. Instead of solving the problem, they make it worse. Selfish extrinsic motivation is reinforced. We suggest measures which clash with conventional wisdom: selecting employees with pro-social intrinsic preferences, de-emphasizing variable pay for performance and strengthening the participation and self-governance of employees. These measures help to increase intrinsically motivated corporate virtue and honesty.
Keywords: 330; Corporate Virtue; fraud; intrinsic motivation; crowding theory; pay for performance; employee participation